2019
DOI: 10.1111/voxs.12515
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for donation among hospital blood donors and their attitude towards voluntary blood donation in State Government Hospitals, Kaduna, Nigeria

Abstract: Background Voluntary blood donation (VBD) is critical to adequate blood supply. Public health facilities in Nigeria rely mostly on replacement blood donation. Motivation for blood donation among hospital donors was assessed, and factors that influence VBD were determined in Kaduna, Nigeria.Methods This is a cross-sectional study on 361 blood donors in three selected hospitals. A structured questionnaire was used to collect information from respondents. Logistic regression was used to identify predictors of VBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The most common motivator to donate blood endorsed by nearly all (94.7%) of the participants in this study is 'to help family or friends in need'. This finding is similar to previous studies in Nigeria [3,15], Ghana [19], Bulgaria [20] and Pakistan [21]. In contrast, in a study by Kasraiana et [17,22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most common motivator to donate blood endorsed by nearly all (94.7%) of the participants in this study is 'to help family or friends in need'. This finding is similar to previous studies in Nigeria [3,15], Ghana [19], Bulgaria [20] and Pakistan [21]. In contrast, in a study by Kasraiana et [17,22].…”
Section: Discussionsupporting
confidence: 91%
“…Nigerian studies have identified the desire to help and save the life of relatives and acquaintances as motivational factors, while poor attitudes of blood bank staff and concerns that donated blood may be sold have been identified as some of the barriers to blood donation [14][15][16]. However, these studies were predominantly among blood donors who are dominated by men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also found similar findings that the leading causes of motivation to donate were family or friends in need of blood -collectivism (86.9%) and altruism (7.3%). 9,10 The qualitative findings also revealed altruism and collectivism as key motivators to voluntary donation. One of the participants from the focused group discussions said "My sister was very sick and in need of blood, my neighbor donated for her.…”
Section: Motivators Of Blood Donation Among the Studentsmentioning
confidence: 88%